Varieties of offshoring in European manufacturing and the role of Central and Eastern European countries - Geodecki, Tomasz; Lubacha, Judyta (Journal of Public Governance, 2026)
Objective: To verify the impact of production offshoring on capital accumulation in the European manufacturing industry. Research Methods & Design: The paper examines 366 European manufacturing industries in the years 2004‒2014 in terms of the impact of offshoring on capital accumulation. The World Input–Output Database (WIOD) was used to construct a model that includes production cost determinants. Two offshoring models were studied: offshore insourcing via foreign direct investments (FDIs) versus offshore outsourcing via trade. In the former, these phenomena largely result from the specificity of FDI drivers as identified by John Harry Dunning in his OLI paradigm (including advantages in terms of ownership, location, and internalisation). Findings: In industries where investors dominate, a clear link can be observed between capital accumulation and the falling prices of intermediate inputs. The latter may be partly due to cooperation with low-cost foreign affiliates from Central and Eastern Europe (CEE) countries, including the declining wage share. On the other hand, in industries dominated by offshoring via trade, the substitution of expensive domestic intermediate inputs and the attendant reduction in the share of wages in value added was the more important factor. Implications: Using the WIOD database to create measures of offshoring effects permits the identification of important reasons for offshoring and the impact of its mechanisms on the labour market. Value Added: Attesting to what extent strategic actions aimed at improving the place of industries in the production network may affect the operating costs of enterprises. The trends outlined in this paper may be treated as an introduction not only to reflecting on offshoring as an efficient tool of capital accumulation but also on the political economy and social sustainability of this process in CEE countries.